Roles of neuroimaging markers and biomarkers in cerebral small vessel disease and their associations with cognitive function - Xiaoqian Song; Xiaoqian Song; Chenyang Jin; Moxin Luan; Xueping Zheng (Frontiers in Neurology)
Cerebral small vessel disease (CSVD) is an intracranial vascular disorder caused by the impairment of cerebral microvessels, with various pathological backgrounds. Currently, a clear and definitive set of diagnostic criteria for CSVD continues to be elusive, and its diagnosis relies primarily on medical history, clinical presentation, brain imaging features, and genetic detection. In clinical practice, no single biomarker was identified. Previous studies have delved into various biomarkers in CSVD and their relationships with cognitive functions, yielding promising candidates. However, drawing a unified and conclusive consensus poses a challenge due to the inherent heterogeneity in research. Therefore, we reviewed the current progression of CSVD biomarkers and their relationship with cognitive functions, mainly including neuroimaging markers and biomarkers related to cerebrospinal fluid (CSF), as well as blood to assist clinicians in diagnosis.